Is the adversarial trial under the Malaysian Criminal Procedure Code compatible with Islamic Law? - Kamarudin, Abdul Rani (2006)
This article discusses and deliberates the nature of adversarial trial in a criminal proceeding based on the Malaysian Criminal Procedure Code which is based on the Common Law and to compare it with Islamic Law. The inherent features of the two legal traditions are scrutinized by highlighting the relevant provisions in the Code relating to trial and compare them with the basic features and objectives of a criminal trial under Islamic law. It can be ascertain whether justice is substantially seen to be done to both the opposing parties under both legal systems. Likewise, this article will also discuss, and determine whether there are any fundamental similarities or irreconcilable differences between Islamic Law and the Malaysian Criminal Procedure Code which actually is based on Common Law. In other words, in a criminal proceeding, whether the adversarial trial under the Common Law is compatible with Islamic Law. The civil law tradition which is notable for its inquisitorial system is also considered to give a more balanced perspective to the discussion. This article also enlightens readers, how the different legal systems operate and one should be doubly careful in doing a complete volte face and be too eager to throw aside a particular legal system that has been proved effective.